LAPORAN KEUANGAN PEMERINTAH PUSAT (LKPP) TAHUN ANGGARAN 2008 MASIH DENGAN ”DISCLAIMER OPINION” - BUDIARTHA, I KETUT (Jurnal Ilmiah Akuntansi dan Bisnis, 2010)
BPK RI (the state auditor body) plays a significant role to materialize and apply the principle of transparency and accountability on state financial report. Interim audit is conducted before the yearly financial audit. During the process of evidences collection, an auditor frequently faces a limitation of audit scope. An auditor must stay independent and look independent to maintain independency on opinion, judgment, as well as recommendation. The purpose of this research is to examine the effect of interim audit, scope of audit, and independency on auditor opinion judgment of auditors of BPK RI Bali Province Representatives. Data are collected using survey method administered to staffs of BPK Bali Province. Data consisting of 44 responses are analyzed using multiple regression model. The result shows that judgment of auditor opinion is able to be explained by variables of interim audit, scope of audit, and independency with value of R2 of 73.4 percent. While t-test result shows that partially the three variables also affect auditor opinion.
Keywords: interim audit, scope of audit, independency, opinion, auditor.